The Level of Knowledge of the Concept of Sustainable Development in Palestine Among Employees of Sports and Government Institutions - Maryam Mohammed Hathnawi; Prof. Riadh Ben Yassine Khalifa (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study aimed to assess the level of knowledge of the concept of sustainable development among employees in sports and government institutions in Palestine and to examine whether gender-based differences exist. Using a descriptive-analytical approach, a questionnaire of (10) items measuring knowledge of sustainable development and its goals was administered to (2040) male and female employees across youth and sports-related institutions in Palestine, including the Higher Council for Youth and Sports, the Palestinian Olympic Committee, relevant ministries, and sports federations. The instrument was validated by experts, with reliability confirmed at Cronbach’s alpha of (0.79) for the knowledge domain, and data were collected in (2022). Statistical analysis involved means, standard deviations, and an independent-samples t-test for gender differences. Findings revealed that the overall knowledge level was moderate, with a mean of (3.22) out of (5), as all (10) items scored at a moderate level. The highest-scoring aspects were recognizing that sustainable development instills environmental ethics (3.32) and enhances awareness of social issues (3.27), while the lowest were recognizing gender equality (3.14) and prior reading on sustainable development (3.11). Results further indicated a statistically significant difference favoring males. Overall, the moderate knowledge level reflects a general but incomplete understanding of sustainable development, highlighting the need to strengthen comprehension of specific aspects, particularly gender equality, through awareness and training programs that would enable institutions to contribute more effectively to achieving sustainability goals.